UJI AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN UNGU (GRAPTOPHYLLUM PICTUM) DENGAN METODE DPPH: Tinjauan Pustaka Sistematis - Quenhita Rindhika Ruriza (2021)
Degenerative disease is a diseases caused by degeneration of the cell function. This disease can be reduced by administering antioxidants. Natural ingredients are used as antioxidants because they are needed to improve the quality of public health with lower costs and ingredients that are easily found in Indonesian nature. This study was to discover the existance of antioxidant activity in Graptophyllum pictum using the DPPH method. The method used is Systematic Review, a research method that uses existing evidence-based research to be reviewed, analyzed, structured evaluated, classified, and categorized. The assessment of journal quality used the checklist of The Joanna Briggs Institue (JBI) Critical Apprasial tools and 6 journals were obtained to assess the antioxidant activity of Graptophyllum pictum which were used as data sources for further study. According to the results of the 6 research journals reviews, the antioxidant activity of Graptophyllum pictum had varying strengths; very strong antioxidants, strong antioxidants, moderate antioxidants and very weak antioxidants, which are affected by the type of solvent and extraction methods.